2017
DOI: 10.1111/papr.12584
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and Developing Sleep Problems: A Prospective Cohort Study on the Relationship to Poor Outcome in Patients Attending a Pain Clinic with Chronic Low Back Pain

Abstract: Sleep problems are common in people with low back pain (LBP), however the mechanisms on how sleep influences pain are complex. To date there is a lack of prospective research on the timings and the development of sleep problems in those who have LBP, such information would be useful to identify individuals at risk of poor outcome. Aims are to investigate the predictive role of sleep problems on self-report recovery and pain intensity using logistic regression reporting Odds Ratios (OR). An observational cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 43 publications
5
44
0
Order By: Relevance
“…Few studies have investigated the influence of sleep problems on the prognosis of chronic LBP. A recent study of patients with LBP showed that co-existing sleep problems lowered the probability of recovering from LBP at 6 months follow-up 7. Furthermore, an observational study of persons with occasional LBP showed that sleep problems increased the risk of developing troublesome LBP at 4 years follow-up 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have investigated the influence of sleep problems on the prognosis of chronic LBP. A recent study of patients with LBP showed that co-existing sleep problems lowered the probability of recovering from LBP at 6 months follow-up 7. Furthermore, an observational study of persons with occasional LBP showed that sleep problems increased the risk of developing troublesome LBP at 4 years follow-up 10.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep problems are common among people with chronic LBP 2–4. It has been shown that insomnia symptoms increase the risk of chronic LBP5 and that poor sleep is associated with subsequent pain intensity6 and persistence of pain7 in people with LBP. Furthermore, experimental studies have revealed a possible pathway between poor sleep and pain by showing that sleep deprivation leads to elevated levels of pro-inflammatory cytokines8 and alterations in central pain processing 9.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, both the treatment of pain intensity given at the pain clinic and the associated emotional disturbances in the form of anxiety and aggression proved to have been effective. Pain is closely linked to the occurrence of emotional disturbances, which is confirmed by the studies of Pakpou et al (2018), Sagheer et al (2013), and Ahmed et al (2013) [24,25,26]. The study of Merrick et al (2012), who did a year-long observation of two rehabilitation management strategies of chronic pain in patients treated at the rehabilitation clinic of the University Hospital of Umeå, Sweden, shows that the patients enrolled in the multimodal rehabilitation program reported a lack of pain symptoms in a statistically significant number of cases (59% vs. 46%).…”
Section: Discussionmentioning
confidence: 61%
“…Other factors such as kinesiophobia, pain catastrophizing, inappropriate beliefs about pain, sleep problems, and depression may also contribute to the central sensitization and pain chronification. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%